Methodology of foreign language training of master's students in the field of energy using innovative technologies - Bilan, Nataliia; Volkova, Natalііa; Fedoreiko, Iryna; Horbatiuk, Roman; Bureha, Nazar; Zahorodnii, Roman; Zamora, Yaroslav (Edelweiss Applied Science and Technology, 2025)
The article highlights the peculiarities of developing the methodology for foreign language training of graduates using innovative technologies and its implementation in the educational process with a practical justification of the results obtained. The study also aimed to determine the level of foreign language competence of future power engineers. The experimental work consisted of three stages, during which the following methods of scientific research were used: analysis, generalization, comparison, modeling, pedagogical experiment, and methods of mathematical statistics. Based on the analysis of scientific and pedagogical works, information and communication, interactive, project-based learning technologies that can ensure high-quality foreign language learning are highlighted. The information and communicative educational environment for foreign language training of future power engineers for the practical implementation of the developed methodology is designed using the method of modeling. During the pedagogical experiment, the effectiveness of using the electronic service Learning Apps in mastering lexical items and repeating grammatical rules; project technologies in activating receptive and productive types of speech activity; and information and communication technologies in objectively assessing the level of foreign language knowledge, skills, and abilities, as well as expanding personal and professional range, was established. The results of the experimental work revealed positive dynamics in the levels of lexical, grammatical, speech, pragmatic, and socio-cultural competences, which are the structural elements of master's students' foreign language competence. The proposed methodology allows for the intensification, optimization, and activation of the process of foreign language training of future power engineers in a blended learning environment.